Pharmacokinetic and pharmacodynamic profile of the sodium‐glucose co‐transporter‐2 inhibitor empagliflozin in young people with Type 2 diabetes: a randomized trial. Issue 8 (6th May 2018) - Laffel, L. M. B.; Tamborlane, W. V.; Yver, A.; Simons, G.; Wu, J.; Nock, V.; Hobson, D.; Hughan, K. S.; Kaspers, S.; Marquard, J.
Abstract: Aims: To assess the pharmacokinetic and pharmacodynamic profile of a single dose of empagliflozin in young people with Type 2 diabetes to identify the appropriate doses for further paediatric development. Methods: We conducted a single‐dose, open‐label, randomized, parallel‐group study with empagliflozin 5 mg, 10 mg and 25 mg in young people with Type 2 diabetes aged 10–17 years. Results: Of 39 participants screened, 27 were randomized and completed the study; their mean (± sd ) age was 14.1±2.0 years and body weight was 96.7±23.5 kg. Compared with similar studies in adults with Type 2 diabetes, the maximum observed plasma concentrations were slightly lower with the 10‐mg and 25‐mg doses, and the area under the plasma concentration–time curve was slightly lower with the 10‐mg but slightly higher with the 25‐mg dose. The adjusted mean increases in urinary glucose excretion were 53 g/24 h (95% CI 32, 74), 73 g/24 h (95% CI 52, 94) and 87 g/24 h (95% CI 68, 107), and the adjusted mean decreases in fasting plasma glucose were 0.9 mmol/l (95% CI –1.6, –0.1), 0.9 mmol/l (95% CI –1.7, –0.2) and 1.1 mmol/l (95% CI –1.8, –0.5) for the 5‐ 10‐ and 25‐mg doses, respectively. There were no serious adverse events and one investigator‐reported drug‐related event (dehydration). Conclusions: After a single oral dose of empagliflozin, adults and young people with Type 2 diabetes had similar exposure–response relationships after adjusting for significant covariates. These data support testing 10‐mg and/or 25‐mg doses of empagliflozin in an upcoming paediatric phase III Type 2 diabetes trial. (ClinicalTrials.gov registration no.: NCT02121483). What's new?: Metformin and insulin remain the only drugs approved for the treatment of young people with Type 2 diabetes, highlighting the need to perform and complete studies with newer glucose‐lowering drugs in the paediatric population. In this paper we report the results of the pharmacokinetics and pharmacodynamics of the sodium‐glucose co‐transporter‐2 inhibitor empagliflozin in young people with Type 2 diabetes, an important first step in identifying the doses of empagliflozin to be used in a future pivotal trial. The results indicate that the 10‐mg and/or 25‐mg doses of empagliflozin may be further investigated in an upcoming paediatric phase III study.